International Data on Measuring Management Practices - Bloom, Nicholas; Lemos, Renata; Sadun, Raffaella; Scur, Daniela; Van Reenen, John (American Economic Review, 2016)
We examine methods used to survey firms on their management and organizational practices. We contrast the strengths and weaknesses of “open ended questions” (like the World Management Survey) with “closed questions” (like the MOPS). For this type of data, open ended questions give higher quality responses, but are more costly than closed question-based surveys.